(untitled) (LIS TODAY, 2023)
Reading is a way to get better knowledge of one’s own experiences and it can be an exciting journey to self-discovery. The purpose of this study is to try to understand the reading habits of undergraduate students of Government Hamidia Arts and Commerce College, Bhopal and to study the effects of internet on their reading habits. The total number of students participating in the survey is 150, and the questionnaire was distributed to them after random sampling. The results reveal whether students enjoy reading, their frequency of reading books, what genre they prefer to read, the factors that influence their reading habits, and impact of the internet (ICT) media on their reading habits.